The Influence Of Experiential Marketing On Customer Loyaltythrough Customer Satisfaction As Intervening Variable - Widowati, Retno; Tsabita, Fitria (Universitas Muhammadiyah Yogyakarta, 2017)
This research investigates the relationship between Experiential Marketing, Customer Satisfaction and Customer Loyalty of The House of Raminten restaurant. One of marketing approach to create customer loyalty is using experiential marketing through sense, feel, think, act, and relateto build relation to customer that reach customer satisfaction and customer loyaltypurposive sampling. The survey with questionaires was conducted to collect the data. By implementing Structural Equation Modeling (SEM) the results indicate that Experiential Marketing significantly influences customer satisfaction, customer satisfaction showed significantly influences Customer Loyalty. Experiential marketing does not significantly direct influence to Customer loyalty. Customer satisfaction plays role as intervening variable between Experiential Marketing and Customer Loyalty.